(untitled) (Swiss Medical Weekly, 2010)
QUESTIONS UNDER STUDY: The profile of the medical profession is changing in terms of employment conditions, attitudes towards the profession and the lifestyle of young physicians. The aim of this study was to investigate (1) what modifications should be made in the specialty-qualification curriculum to allow for a better balance of career and personal life, (2) what institutional conditions and (3) what personal attitudes and behaviour are required for physicians to successfully combine career and family. METHODS: As part of a prospective survey on the career development of Swiss medical school graduates (SwissMedCareer Study) begun in 2001, 526 physicians (274 females, 52.1%; 252 males, 47.9%) participated in the sixth assessment in 2010. The graduates were asked by mail-out questionnaires to provide free response answers to the three questions formulated above. Their statements were transcribed, content categories were inductively formulated for each question, and their descriptions were written down in a code manual. Responses were encoded according to the said manual and assigned to content categories (Mayring’s content analysis). Frequency distributions were given for categories and tested with chi-square tests for gender differences. RESULTS: The 526 participants made 457 statements on the first question, 1,038 on the second, and 937 on the third. Content analysis of the physicians’ answers yielded nine categories dealing with desired changes to the specialty qualification curriculum, eight categories addressing changes in institutional conditions, and nine categories concerning personal attitudes and behaviour. Of all responses to the first question, 70% fell into the top three ranking categories of “specialty qualification requirements”, “part-time jobs” and “structured residency programmes”. The three top-ranking categories (“childcare facilities”, part-time jobs”, “working hours”) yielded by responses to the second question accounted for 87% of the statements. Distribution of the responses concerning personal attitudes and behaviour was more widespread across the nine categories. Marked organisational skills and the ability to adapt flexibly to various everyday demands at work and home were recognised as essential in one third of the statements. CONCLUSION: In order to meet the needs of the medical profession’s changing profile in terms of feminisation and modern lifestyle, changes must be initiated at different levels. Postgraduate training must be provided in structured programmes, and curriculum requirements must be revamped. Hospital authorities should offer more part-time jobs as well as adequate and affordable childcare facilities for physicians with young children. Physicians should engage critically and to a greater extent with the continued development of their profession.